Coaching and mentoring. 14 : Theory and practice - Garvey, Bob (London : SAGE Publications, 2017)
This book is not available as a print inspection copy. To download an e-version click here or for more information contact your local sales representative. Drawing on extensive research and the authors' own experiences as coaches and mentors, the book offers a critical perspective on the theory and practice of coaching and mentoring. The Third Edition is split into four parts and has been updated to include the contemporary debates, issues and influences in the field. It features a collection of new international case-studies, drawn from the USA, Africa, Asia and South America, along with an increased emphasis on current topics such as internal coaching schemes, e-technologies and social media. In addition to these features, there are four new chapters: Perspectives on Coaching and Mentoring from around the Globe - Comparing case studies written by practitioners in locations around the world. The Skilled Coachee - An examination of the role of coachee in the coaching and mentoring process. Question of Ethics - A chapter devoted to the ethical issues inherent in coaching and mentoring. Towards a Meta-Theory - A chance for the reader to conceive new ways to engage with theory and practice. The book is complemented by a companion website featuring a range of tools and resources for instructors and students, including PowerPoint slides, flash-cards and access to full text SAGE Journal articles. Suitable reading for students on coaching and mentoring modules.
Keywords: elektronické knihy; electronic books; Business & Management -- Coaching